Contribution to multi-physical studies of small synchronous-reluctance machine for automotive equipment - Mohd Azri Hizami, Rasid (2016)
Due to environmental concern related to CO_{2} emissions, automobile manufacturers has been increasingly engaging in electrifying multiples on-board applications. Functions that are being electrified involve crucial and complex applications such as clutches, power steering, assisted brakes and others. Furthermore, these functions are often placed in a particularly challenging environment in terms of spaces, thermal, vibration and acoustic. As results, research on electrical motors to find the most suitable motor to a given applications has been intensified. In this environment, machines optimal design requires simultaneous consideration of numerous physical phenomena ; both in terms of expected performance and constraints to be respected. The physics that can be affected includes the electromagnetic / electromechanical performance, thermal behavior and vibro-acoustic behavior. Among a large choice of machine, with the manufacturer cost and manufacturing concern taken into account, the synchronous reluctance machine with segmented rotor has been found to be particularly interesting for application with severe ambient temperature and encumbrance limitation. This study has therefore as objectives to evaluate the capacity of the synchronous reluctance machine in all physics mentioned and eventually shows the interaction between these physics, thus performance alteration of the machine operated in automobile equipment environment. Multi-physics model were developed and confronted to experimental validations using a prototype machine that was designed for an electrical clutch. Using the validated model, different performance figures of synchronous reluctance machines with different rotor topologies were compared. Resulting from the study, valid electromagnetic, electromechanical, thermal and vibro-acoustic models are now available to be used as tools in future machine design. The synchronous reluctance with segmented rotor prototype machine has been shown to be capable to be used in the electrical clutch application studied in particular. Following performance evaluations in different physics, suggestions of improvements have also been proposed.